BIMG-11. PHARMACODYNAMIC EVALUATION OF IDH AND EGFR INHIBITION IN HUMAN GLIOMAS USING MOLECULAR MRI. (25th March 2021) - Ellingson, Benjamin; Yao, Jingwen; Hagiwara, Akifumi; Nathanson, David; Oughourlian, Talia; Everson, Richard; Salamon, Noriko; Pope, Whitney; Nghiemphu, Phioanh; Lai, Albert; Liau, Linda; Cloughesy, Timothy
Abstract: Metabolic differences are inherent to specific glioma subtypes and can be altered using targeted treatments, including IDH and EGFR inhibition. Using a large cohort of patients scanned at UCLA and other centers over the last 5 years, we demonstrate that IDH, 1p19q, and EGFR alterations uniquely contribute to alterations in glycolysis and oxygen utilization using a clinically available molecular MRI technique termed amine chemical exchange saturation transfer spin-and-gradient-echo echoplanar imaging (CEST-SAGE-EPI). Our data shows that CEST-SAGE-EPI estimates of tumor acidity are strongly associated with the degree of glycolysis as evaluated with direct pH measurements, quantitative IHC, bioenergetics experiments, and correlations with 18F-FDG PET images. Data further reveals that IDH wild type gliomas have higher acidity and oxygen utilization compared with IDH mutant gliomas, 1p19q non-codeleted gliomas (astrocytomas) have higher tumor acidity compared to 1p19q codeleted gliomas (oligodendrogliomas), and EGFR amplified gliomas have higher oxygen utilization compared with non-amplified gliomas. Additionally, phase II clinical trial data suggests successful IDH inhibition results in an early and measurable increase in tumor acidity and further reduction in oxygen utilization, signifying suppression of oxidative phosphorylation and/or glutaminolysis in favor of glycolysis. Alternatively, phase II clinical trial data suggests successful EGFR inhibition with brain penetrant agents results in early reductions in tumor acidity and 18F-FDG PET uptake, consistent with a reduction in glycolysis. Data also indicates that continual increases in tumor acidity during routine follow-up after initial therapeutic changes results in uniformly worse outcomes in all tumor subtypes under all mentioned treatment scenarios.